Legal challenges of cross-border insolvencies in sub-saharan Africa with reference to Tanzania and Kenya: a framework for legislation and policies - Masoud, Benhajj Shaaban (Nottingham Trent University, 2012)
Although a substantial body of literature has developed in recent years in the area of cross-border insolvency, this scholarship has been dominated by scholars from the United States and Europe, so that a perspective from most of Sub-Saharan African (SSA) countries is lacking. This study addresses this perspective. It makes an in-depth examination and discussion of the challenges that SSA countries face in reform and application of cross-border insolvency law given the ever-growing multinational trade and investment. The study focuses on the risk of failure of SSA legislative processes to properly address the potential challenges of cross-border insolvencies in a manner that is sensitive to the local contexts and which provides a balance with international insolvency benchmarks. It examines cross-border insolvency theories; the global drivers for convergence of insolvency law through global insolvency norms; and the implications for cross-border insolvency regulations arising from cross-border trade and investment arrangements, such as the bilateral investment treaties, before considering the state and future of the legislative frameworks of SSA countries.
Nottingham Trent Institutional Repository (IRep) https://core.ac.uk/works/7793942/
Keywords: Cross-border Insolvency; Insolvency; International insolvency

Essays in corporate restructuring, reputation and law - Polo, Andrea (Oxford University, 2012)
This dissertation consists of three essays which examine topics at the intersection of law and finance. The first essay investigates the role of regulatory sanctions and reputational damage in financial markets. We study the impact of the announcement of enforcement of financial and securities regulation by the UK’s financial regulators on the market price of penalized firms. We find that reputational sanctions are very real: their stock price impact is on average almost 9 times larger than the financial penalties imposed. Furthermore, reputational losses are confined to misconduct that directly affects parties who trade with the firm (such as customers and investors). In the second essay we analyze the costs and benefits associated with secured creditor control in bankruptcy. We do it by studying the highly contested practice of UK pre-packs, where a deal to sell the business is agreed before publicly entering into bankruptcy. Contrary to widespread criticism that this procedure leads to collusion, we find no evidence of exploitation of conflict of interests and we find that it preserves the value of the business and maximizes recovery in circumstances in which a public announcement of bankruptcy would destroy value. In small businesses where secured creditors are concentrated the benefits of their control seem to outweigh the costs. Finally, in the last essay we examine whether mandatory shareholder voting prevents wealth destruction in corporate acquisitions. We study the UK setting where all large transactions must have shareholder approval. We observe that such Class 1 transactions always get consent. Nevertheless, there is a striking difference between the performance of acquirers between Class 1 and other transactions. The finding is most pronounced for transactions in a narrow neighbourhood of the size threshold, and is robust to a large set of controls for confounding effects.